Use of salivary cortisol and cortisone in the high‐ and low‐dose synacthen test. (29th November 2017) - Elder, Charlotte J.; Harrison, Robert F.; Cross, Alexandra S.; Vilela, Ruben; Keevil, Brian G.; Wright, Neil P.; Ross, Richard J.
Summary: Context: Salivary cortisone reflects serum cortisol levels, is more sensitive than salivary cortisol at lower values of serum cortisol and is noninvasive. Objective: To investigate the relationship between serum cortisol and salivary cortisol and cortisone following low‐ and high‐dose synacthen. Design and setting: Prospective pharmacodynamic studies in clinical research facilities. Participants and intervention: Thirty‐five dexamethasone‐suppressed, healthy adult males underwent an intravenous synacthen test: N = 23 low‐dose (1 mcg), N = 12 high‐dose (250 mcg). Paired serum and salivary samples were taken at 15 sampling points over 120 minutes. Main outcome measure: Serum cortisol and salivary cortisol and cortisone were analysed for correlations and by a mixed‐effects model. Results: At baseline, the correlation between serum cortisol and salivary cortisol was weak with many samples undetectable ( r  = .45, NS), but there was a strong correlation with salivary cortisone ( r  = .94, P  < .001). Up to 50 minutes following synacthen, the correlation coefficient between serum cortisol and salivary cortisol and cortisone was <0.8, but both had a stronger correlation at 60 minutes (salivary cortisol r  = .89, P  < .001, salivary cortisone r  = .85, P  < .001). The relationship was examined excluding samples in the dynamic phase (baseline to 60 minutes). Salivary cortisol and cortisone showed a close relationship to serum cortisol. Salivary cortisone showed the stronger correlation: salivary cortisol r  = .82, P  < .001, salivary cortisone r  = .96, P  < .001. Conclusion: Following synacthen, both salivary cortisol and cortisone reflect serum cortisol levels, but there is a lag in their rise up to 60 minutes. The results support further research for possible future use of a 60‐minute salivary cortisone measurement during the synacthen test.